There is no solution without national strategy about truth and reconciliation - Marjanović Zdravko (Temida)
The society for tolerance was set up as a peace group in 1993, which means that it has been dealing with the issue of reconciliation ever since it came into being. The two kinds of activities on the reconciliation plan have so far been the following: Fieldwork in Eastern Slavonia and Western Srem as well as in Bosnia and Herzegovina. Activities in the local communities. Current activities include the implementation of the agreement on cross-border cooperation of the local authorities, entrepreneurs and the civil sector of four countries: Hungary, Croatia, Bosnia and Herzegovina and Serbia and Montenegro. As we believe that the problem is not only related to the truth (the precondition for reconciliation) during the latest wars, but that those roots are far deeper, our plans are to activate our long-standing project of the Social club, through the "House for multiculturalism and regional cooperation" that we formed by signing an agreement with some NGO-s in Croatia and Hungary. The project includes encounters of the citizens primarily of the children and of the young, in order to openly discuss issues related to their everyday lives, one of the most important being reconciliation. In this process, we also perceive the process of rehabilitation through dispersing stereotypes that were created as a consequence of the long-existing absence of confrontation with the truth.